Archetypal type II and III Toxoplasma gondii oocysts induce different immune responses and clinical outcomes in experimentally infected piglets - Largo-de la Torre, Andrea; Diezma-Díaz, Carlos; Calero-Bernal, Rafael; Atencia-Cibreiro, Gabriela; Sánchez-Sánchez, Roberto; Ferre, Ignacio; Regidor-Cerrillo, Javier; Ortega-Mora, Luis Miguel (Frontiers in Immunology, 2022)
Livestock animals, such as swine, are an important source of Toxoplasma gondii in the human population. Currently, there is limited knowledge regarding the potential influence that the T. gondii genotype might exert on establishing infection in swine. Herein, we investigated the role of 2 T. gondii isolates, type II and III, representative of the genotypes circulating in Europe, in the immune responses and infection dynamics in piglets. Recently obtained oocysts (103) from the T. gondii field isolates TgShSp1 (type II, ToxoDB genotype #3) and TgShSp24 (type III, ToxoDB #2) were used for oral infection. Thirteen 50-day-old female piglets of the Landrace-Large White crossbreed were randomly allocated into three different groups: Group 1 (G1, n=5), inoculated with TgShSp1; Group 2 (G2, n=5), inoculated with TgShSp24; and Group 3 (G3, n=3), a noninfected control group. Clinical signs were monitored daily until 42 days post-infection (dpi) when piglets were euthanized. Blood samples were collected weekly to test the cellular immune response in parasite-stimulated peripheral blood and specific IgG, IgG1 and IgG2 responses in sera. Parasite distribution and burden were evaluated in target tissues using a mouse bioassay and quantitative RT‒PCR (qPCR). Apathy and a moderate decrease in feed consumption were observed in G1 and G2 piglets between 5 and 8 dpi, coinciding with fever (>40 °C). G2 piglets had higher temperatures for a longer duration. Using mouse bioassay and qPCR, the detection frequency was higher in G2 vs. G1, and the highest parasite burdens in target tissues were also found in G2. Seroconversion was detected at 14 dpi in both infected groups, but higher antibody levels were observed in G2 piglets. Cytokine analyses revealed the production of IL-8, IL-1β and IFN-ɤ from 7 dpi in both infected groups. Moreover, IL-12 was produced from 7 dpi in G1 and from 14 dpi in G2. Levels of IL-8 were higher in G2, but IL-1β, IL-12 and IFN-ɤ were higher in G1 at 14 dpi. This cytokine profile reveals a predominant proinflammatory response that could be involved in limiting T. gondii infection in piglets, although it is more efficient against TgShSp1 type II-driven infection.